Edukasi Pencegahan dan Penanganan Penyakit Maag Siswa SMP Negeri Satap 11 Konsel - Muhammad Fitrawan, La ode; Yamin, Yamin; F. S, Muh Sultan; Muliyana, Muliyana; Resti, Resti; N, Sherliyanti; M, Tirsa Arruan (Universitas Pahlawan Tuanku Tambusai, 2025)
Gastric acid disease is often suffered by young people caused by an unhealthy lifestyle. Gastric acid occurs due to the increase in esophageal and esophageal stomach acid which causes the stomach to become irritated. The purpose of the activity is to increase knowledge and broaden the insight of students of SMP Negeri Satu Atap 11 Konawe Selatan. The form of activity is in the form of a presentation in providing education on the prevention and treatment of ulcers. here was an increase in knowledge with a Pre-Test value of 40% and a Post-Test value of 60%, meaning that the delivery method used was very effective.